1993
DOI: 10.1002/qua.560480203
|View full text |Cite
|
Sign up to set email alerts
|

Early stages of LiX, BeH2X, and BH3X pyrolysis (X stands for NH3 or OH2): A theoretical study of weak dative complex stability

Abstract: In this work, we study theoretically the thermal decomposition of weak dative complexes (namely, the complexes between BH3, BeH2, or LiH and ammonia or water). The most accurate calculations have been carried out at the ~~4sdtq/6-311+ +G(3df,2p) level on MP2fu11/6-31c** fully optimized geometries. The transition structures for hydrogen evolution are described. The rate constants were obtained using conventional transition-state theory. Stability conditions for the complexes were considered. Water complexes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
(23 reference statements)
0
11
1
Order By: Relevance
“…40.0 kcal/mol. 5 Incidentally, the N−B bond of AB cleaves at a cost of 23.0 kcal/mol. 6 Experimentally it is known that the onset of AB decomposition in solid state occurs at 120 °C under atmospheric pressure, whereas it was shown by Geanangel et al and other experimental groups that the decomposition of AB initiates at much lower temperatures in ether solvents.…”
Section: Uncatalyzed Thermal Dehydrogenation Of Ab In Organic Solventsmentioning
confidence: 99%
See 4 more Smart Citations
“…40.0 kcal/mol. 5 Incidentally, the N−B bond of AB cleaves at a cost of 23.0 kcal/mol. 6 Experimentally it is known that the onset of AB decomposition in solid state occurs at 120 °C under atmospheric pressure, whereas it was shown by Geanangel et al and other experimental groups that the decomposition of AB initiates at much lower temperatures in ether solvents.…”
Section: Uncatalyzed Thermal Dehydrogenation Of Ab In Organic Solventsmentioning
confidence: 99%
“…Sana and co-workers used gas-phase computations to predict that the first equivalent of H 2 loss occurs through a very high activation energy of 40.0 kcal/mol. 5 Later, Dixon et al suggested that BH 3 produced from the dissociation of the N−B bond in AB, can act as a Lewis acidic catalyst and brings down the activation barrier (ca. 20.9 kcal/mol) for AB dehydrogenation (see Scheme 1).…”
Section: Uncatalyzed Thermal Dehydrogenation Of Ab In Organic Solventsmentioning
confidence: 99%
See 3 more Smart Citations